Concept of small states, current problems and future prospects (with special reference to the Caribbean) - Farrell, Trevor M.A. ([s.n.] [S.l.], 1991)
Suggests a definition of a small state. Looks at the significance of small size and what it implies. Examines current problems, organizations, management and human resources, and reviews future prospects.